2019
DOI: 10.3390/rs11222604
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Surface Wind Asymmetry in Tropical Cyclones over the Northwest Pacific Ocean Using SMAP Observations

Abstract: Tropical cyclone (TC) surface wind asymmetry is investigated by using wind data acquired from an L-band passive microwave radiometer onboard the NASA Soil Moisture Active Passive (SMAP) satellite between 2015 and 2017 over the Northwest Pacific (NWP) Ocean. The azimuthal asymmetry degree is defined as the factor by which the maximum surface wind speed is greater than the mean wind speed at the radius of the maximum wind (RMW). We examined storm motion and environmental wind shear effects on the degree of TC su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…TC intensity and storm structure are not unrelated}strong storms are more symmetric than weaker ones Jiang 2016, 2017;Sun et al 2019). While those aforementioned variables are originally derived for TC intensity prediction (Lee et al 2015(Lee et al , 2016Yang et al 2020), they are suitable for storm structure prediction as well.…”
Section: A Tropical Cyclones and Their Environmentmentioning
confidence: 99%
“…TC intensity and storm structure are not unrelated}strong storms are more symmetric than weaker ones Jiang 2016, 2017;Sun et al 2019). While those aforementioned variables are originally derived for TC intensity prediction (Lee et al 2015(Lee et al , 2016Yang et al 2020), they are suitable for storm structure prediction as well.…”
Section: A Tropical Cyclones and Their Environmentmentioning
confidence: 99%
“…They built up a new parametric model for surface wind speed of TC. Recently, Sun et al (2019) found that the surface wind asymmetry degree decreases with increasing TC intensity but increases with increasing TC translation speed. This relationship is found for tropical storms and super typhoons, while typhoons and severe typhoons do not.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical comparisons between SMAP-derived wind speeds and SFMR measurements, from eight TCs during 2015, have shown that the standard deviation of wind speed was 3.11 m/s for wind speeds up to 70 m/s [19]. Moreover, as an application, SMAP wind data acquired in the Northwest Pacific Ocean have been used to examine TC surface wind asymmetry [22].…”
Section: Introductionmentioning
confidence: 99%